Atomically Dispersed Indium‐Copper Dual‐Metal Active Sites Promoting C−C Coupling for CO2 Photoreduction to Ethanol. Issue 40 (25th August 2022) - Shi, Hainan; Wang, Haozhi; Zhou, Yichen; Li, Jiahui; Zhai, Panlong; Li, Xiangyang; Gurzadyan, Gagik G.; Hou, Jungang; Yang, Hong; Guo, Xinwen
Abstract: Photoreduction of CO2 to C2+ solar fuel is a promising carbon‐neutral technology for renewable energy. This strategy is challenged by its low productivity due to low efficiency in multielectron utilization and slow C−C coupling kinetics. This work reports a dual‐metal photocatalyst consisting of atomically dispersed indium and copper anchored on polymeric carbon nitride (InCu/PCN), on which the photoreduction of CO2 delivered an excellent ethanol production rate of 28.5 μmol g −1 h −1 with a high selectivity of 92 %. Coupled experimental investigation and DFT calculations reveal the following mechanisms underpinning the high performance of this catalyst. Essentially, the In−Cu interaction enhances the charge separation by accelerating charge transfer from PCN to the metal sites. Indium also transfers electrons to neighboring copper via Cu−N−In bridges, increasing the electron density of copper active sites. Furthermore, In−Cu dual‐metal sites promote the adsorption of *CO intermediates and lower the energy barrier of C−C coupling. Abstract : Atomically dispersed In−Cu metal pairs anchored on polymeric carbon nitride catalysts (InCu/PCN) were designed and produced by a facile thermal polymerization approach to support photocatalytic CO2 reduction to ethanol. The metal pairs exert synergistic interactions that enhance the activity and adsorption of metal sites to promote C−C coupling and subsequent formation of ethanol.